Blockade of CCL24 with a monoclonal antibody ameliorates experimental dermal and pulmonary fibrosis. Issue 9 (25th September 2019) - Mor, Adi; Segal Salto, Michal; Katav, Avi; Barashi, Neta; Edelshtein, Victoria; Manetti, Mirko; Levi, Yair; George, Jacob; Matucci-Cerinic, Marco
Abstract : Objectives: We aimed to assess the expression of the CCL24 chemokine in systemic sclerosis (SSc) and to evaluate the possible pathogenic implications of the CCL24/CCR3 axis using both in vitro and in vivo models. We further investigated the efficacy of an anti-CCL24 monoclonal antibody (mAb), CM-101, in inhibiting cell activation as well as dermal and pulmonary inflammation and fibrosis in experimental animal models. Methods: We used ELISA and fluorescence immunohistochemistry to determine CCL24 levels in serum and CCL24/CCR3 expression in skin biopsies of SSc patients. Skin fibroblasts and endothelial cells treated with CCL24 or SSc serum with or without CM-101 were used to follow cell activation and differentiation. Prevention and treatment in vivo bleomycin (BLM)-induced models were used to evaluate experimental dermal and pulmonary fibrosis progression following treatment with the CM-101 mAb. Results: CCL24 circulating levels were significantly elevated in SSc patients. CCL24/CCR3 expression was strongly increased in SSc skin. Blockade of CCL24 with CM-101 significantly reduced the activation of dermal fibroblasts and their transition to myofibroblasts induced by SSc serum. CM-101 was also able to significantly inhibit endothelial cell activation induced by CCL24. In BLM-induced experimental animal models, CM-101 profoundly inhibited both dermal and pulmonary fibrosis and inflammation. Conclusions: CCL24 plays an important role in pathological processes of skin and lung inflammation and fibrosis. Inhibition of CCL24 by CM-101 mAb can be potentially beneficial for therapeutic use in SSc patients.